Application and Efficacy of Super-Magnifying Endoscopy for the Lower Intestinal Tract - Naoki Hosoe; Haruhiko Ogata (Korean Society of Gastrointestinal Endoscopy, 2016)
Endoscopy plays a significant role in the diagnosis, management, and surveillance of colorectal cancer (CRC) and inflammatory bowel diseases (IBDs). Moreover, magnifying endoscopy and image-enhanced endoscopy has a crucial role in the clinical setting. Recently, a super-magnifying endoscope has been developed, and two devices, confocal laser endomicroscopy (CLE) and an endocytoscopy system (ECS), which allow in vivo microscopic inspection of the microstructural mucosal features of the gastrointestinal tract, are currently available. Studies on the use of ECS in CRC were reported by a Japanese group. Additionally, a few studies on the use of ECS in IBD have been reported. CLE has been shown to be reliable in assessing the activity of the disease in IBDs in both ulcerative colitis and Crohn's disease. Various published studies evaluated the use of CLE during colonoscopy to distinguish colorectal polyp pathology and neoplasia. However, these studies are heterogeneous, and further evidence is necessary to confirm the efficacy of CLE.